Peranan Lsm Aliansi Perempuan Merangin Memberikan Pendampingan KDRT Jenis Kekerasan Fisik Berbasis Gender Sebagai Wujud Pelaksanaan UU No. 23 Tahun 2004 - Selvia, Lola; Salam, M; Simamere, Tohap Pandapotan (Citizenship Education, Faculty of Education, Jambi University, 2022)
Based on the results of preliminary observations made by researchers at the Merangin Women's Alliance NGO, it shows that the level of cases of domestic violence experienced by women in the assisted areas of the Merangin Women's Alliance is still quite high and the role of assistance given from non-governmental organizations the Women's Alliance of Merangin to victims of domestic violence still not running optimally, due to various factors that exist within the institution. The purpose of this study is to find out the role of assistance provided by the Merangin Women's Alliance NGO for Victims of Domestic Physical Violence which focuses on women or gender as a form of implementing Law no. 23 of 2004. This research uses qualitative data collection methods in the form of observation, interviews and documentation. The data analysis technique in this study is descriptive qualitative with 3 stages of data analysis namely data reduction, data presentation and drawing conclusions. This research was carried out in 4 stages, namely the preparation stage, the field implementation stage, and the data analysis stage. The results of this study indicate that the Merangin Women's Alliance does not play a proper role as a companion, this can be seen from the 4 indicators in this study, namely 1) the accompaniment factor, APM does not fulfill four roles in the mentoring process, namely as an advocate, mediator, enabler, and motivator . 2) legal factors and laws, APM has not fulfilled the principles of victim protection and articles 22 and 23 concerning victims' rights. 3) the factor of public facilities and facilities, the facilities and facilities owned by APM have not been able to support assistance programs such as the unavailability of safe houses, transportation, and inadequate sources of funds. 4) the community awareness factor, the community is not yet aware of the existence of APM as a companion, the community has a bad view of APM which is considered the cause of divorce between husband and wife.